Pavel Ivanovich Melnikov as Writer and Ethnologist - Martynova, Yulia A.; Martynov, Dmitry E.; Valeev, Ramil M.; Abidullin, Alim M. (Journal of History Culture and Art Research, 2017)
This article is devoted to one of the aspects of intellectual heritage of P. Melnikov. Pavel Ivanovich Melnikov (1819-1883) was an ethnographer-fiction writer who based the descriptions on big actual and documentary material, giving it art and literary interpretation. His main ethnographic work is the "Mordva sketches" published in 1867 in the Russian Bulletin magazine, but not finished. The analysis of his publications shows that actually the ethnography of mordva had no self-sufficing value for P. I. Melnikov. Melnikov shared the idea of Slavic cultural and historical type, general for Slavophiles-pochvenniks, which during historical development assimilate Finno-Ugric tribes. The article is based on application of a comparative method, and comparison to N. Danilevsky’s treatise "Russia and Europe" allowed to draw a conclusion that Melnikov and Danilevsky’s approach concerning situation "of foreigners" in the Russian Empire coincided in a position concerning paganism. Traditional beliefs of the people of the Volga region were considered by them as reflection and memory of ancient Slavic paganism. The historical past of Slavs and finno-ugrs was considered by Melnikov-Pechersky as the general, and modern condition of traditional family institutes and pagan religious representations seemed to them the direct evidence of old Slavic common life. From the point of view of modern historical science Melnikov-Pechersky came to a right conclusion about the early beginning of a Salvic incorporation of the Finno-Ugric population of the Volga region. Their descriptions of life and religion of mordva keep value of the important primary source. This question occupied Danilevsky in the last turn. This study can be of interest to ethnographers and researchers of the Russian social thought of the 19th century.